A feasibility study of the impact of a communication-skills course, 'Empowered Conversations', for care partners of people living with dementia. (November 2021) - Morris, Lydia; Innes, Anthea; Smith, Emma; Williamson, Tracey; McEvoy, Phil
Objectives: To examine the feasibility, acceptability and impact of an experiential course for family care partners of people living with dementia, Empowered Conversations (EC). This study aimed to assess the impact of participation in an EC course on care partner stress levels, communication and mentalization (a form of relational-based empathy). Method: This study uses an uncontrolled pre–post-follow-up design. Follow-up was at 4-months after the initial EC session where baseline data were collected. One hundred and fifty-nine care partners were recruited. EC is a training course that has been designed to improve care partner communication, well-being and relationships. It is based on an integrative framework that targets the specific psychological, relationship and communication needs of carers. This framework informs targeted strategies and interactive exercises that facilitate carers to consider the goals and emotions of those they are caring for, alongside their own goals and emotions, and to use this to maximize good communication. Results: Stress was significantly reduced across the three time points. Communication significantly improved across time. There were no significant changes in reflective functioning (mentalization). Discussion: This study provides preliminary evidence that a communication-skills training course for care partners of people living with dementia is an acceptable and feasible intervention and has an impact both post-intervention and at follow-up. These findings require validation in a rigorous, randomized study.